Comparative evaluation of four rapid diagnostic tests that detect human Trypanosoma cruzi-specific antibodies to support diagnosis of Chagas Disease in urban population of Argentina - Rivero, Rocío (2024)
Chagas disease (CD), caused by the parasite Trypanosoma cruzi, is the most important endemic anthropozoonosis in Argentina. Since 2010, the World Health Organization has highlighted the urgent need to validate diagnostic systems that allow rapid detection of T. cruzi, infection in primary healthcare centers. Serological rapid diagnostic tests (RDTs) for T. cruzi, infection could be used to improve case management, as RDTs do not require specialized laboratories or highly trained staff to use them. We aimed to generate unbiased performance data of RDTs in Argentina, to evaluate their usefulness for improving T. cruzi, diagnosis rates